LEARNERS’ PROBLEMS IN TRANSCRIBING WORDS IN CONNECTED SPEECH - Pininta Veronika Silalahi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
This study is intended to investigate the difficulties encountered by the students of English department in transcribing words in connected speech where assimilation occurs. The assimilation investigated is limited to alveolars /t, d, n) to the neighbouring sound palatal /j, k,g/. Pronouncing words in connected speech is one of the problems that show up in learning EFL. The way words are spoken in isolation and in connected speech may differ significantly. Dealt with the difference, there are two questions to answer in this study. Question one is how students transcribe words in connected speech where assimilation occurs; question two is to describe what sound is assimilated to what sound. To answer the question of the study, descriptive qualitative design is applied. Data were collected from 50 students by giving 7 sentences to transcribe where assimilation occurs in a part of the sentences. Students were asked to transcribe the whole sentences and describe what sound has been assimilated to what sound. The result shows that 18 students can transcribe correctly the phonetic transcription of the assimilated sounds and describe what sound is assimilated to what sound. There are 32 students who transcribe the sentences as isolated words and cannot show where assimilation occurs. Thus, there is no description of the assimilation by these students. It leads to say that knowledge of pronouncing words in connected speech is poor. This suggests improvement by giving more practices in pronouncing not only individual words but words in connected speech. Students also need listening exercises to crosscheck the transcription they make while listening.